2022
DOI: 10.5802/crgeos.104
|View full text |Cite
|
Sign up to set email alerts
|

No direct effect of F, Cl and P on REE partitioning between carbonate and alkaline silicate melts

Abstract: This study presents new insights into the effects of halogens (F and Cl) and phosphorous (P) on rare earth element (REE) partitioning between carbonatite and alkaline silicate melts. F, Cl and P are elements that are abundant in carbonatites and alkaline magmatic systems and they are considered to play an important role on the REE behaviour. Nonetheless, their effect on REE partitioning between carbonate and alkaline silicate melts has not yet been constrained.Here we present new experimental data on REE parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…However, no clear correlation between 𝐷 𝐻𝐹𝑆𝐸 𝐶𝑀/𝑆𝐿 and the concentration of Fand SO 4 2in the carbonatitic melt has been observed so far, as can be seen in Supplementary Figure S4. This lack of correlation is consistent with previous findings (Nabyl et al, 2021). HFSEs tend to concentrate in silicate melts (𝐷 𝐻𝐹𝑆𝐸 𝐶𝑀/𝑆𝐿 < 1), which can coexist with both F -/SO 4 2--rich and F -/SO 4 2--poor experimental runs.…”
Section: Trace Elements Partitioning Between Carbonatitic and Silicat...supporting
confidence: 92%
See 3 more Smart Citations
“…However, no clear correlation between 𝐷 𝐻𝐹𝑆𝐸 𝐶𝑀/𝑆𝐿 and the concentration of Fand SO 4 2in the carbonatitic melt has been observed so far, as can be seen in Supplementary Figure S4. This lack of correlation is consistent with previous findings (Nabyl et al, 2021). HFSEs tend to concentrate in silicate melts (𝐷 𝐻𝐹𝑆𝐸 𝐶𝑀/𝑆𝐿 < 1), which can coexist with both F -/SO 4 2--rich and F -/SO 4 2--poor experimental runs.…”
Section: Trace Elements Partitioning Between Carbonatitic and Silicat...supporting
confidence: 92%
“…Both our experiments and previous partitioning experiments have demonstrated that immiscibility processes between silicate and carbonatitic melts can result in the depletion of HFSEs in carbonatitic melts, depending on varying temperature, pressure, and compositional conditions (Martin et al, 2013;Nabyl et al, 2020;Veksler et al, 1998;Veksler et al, 2012). The newly obtained 𝐷 𝐻𝐹𝑆𝐸 𝐶𝑀/𝑆𝐿 in this study are consistent with recent partitioning experiments (Martin et al, 2013;Nabyl et al, 2021;Nabyl et al, 2020), but significantly higher than the experimental results of Veksler and coworkers (Veksler et al, 1998;Veksler et al, 2012). Noteworthy, our experiments show that HFSE partition coefficients essentially vary in response to changes in the melt composition, especially the SiO 2 content (Figure 2).…”
Section: Parameters Controlling the Partitioning Behavior Of High Fie...supporting
confidence: 92%
See 2 more Smart Citations
“…First, REE will strongly partition to primary mantle-derived carbonatite melts (Foley et al, 2009). Second, carbonatite melts strongly sequester REE when form by immiscibility (Nabyl et al, 2020(Nabyl et al, , 2021. Third, when a carbonatite melt reaches the upper crust and begins differentiating, REE are highly incompatible and will be strongly enriched in residual brine-melts (Anenburg et al, 2020(Anenburg et al, , 2021.…”
Section: What Is the Ree Source?mentioning
confidence: 99%